2021
DOI: 10.3390/vaccines9101090
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Cross-Sectional Study Assessing Self-Reported Adverse Events following Immunization (AEFI) of the COVID-19 Vaccine in Bangladesh

Abstract: Background: The Oxford–AstraZeneca vaccine (Covishield) was the first to be introduced in Bangladesh to fight the ongoing global COVID-19 pandemic. As this vaccine had shown some side-effects in its clinical trial, we aimed to conduct a study assessing short-term adverse events following immunization (AEFIs) in Bangladesh. Method: A cross-sectional study was conducted on social and electronic media platforms by delivering an online questionnaire among people who had taken at least one dose of the COVID-19 vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
6
22
2
Order By: Relevance
“…In our study, less than half of the participants (47.6%) experienced at least one side effect while remaining study participants (52.38%) experienced more than one side effect. Our study results confirmed that most of the side effects were mild in nature as have been observed in other studies conducted elsewhere ( Shrestha et al, 2021 ; Konu et al, 2021 ; Watcharananan et al, 2022; Sultana et al, 2021 ) including in some African settings ( Konu et al, 2021 ). Our findings of odds of women experiencing more acute and severe AEFI from the Covishield vaccine (ChAdOx1 nCoV-19 vaccine) than males has also been observed in Thailand (Watcharananan et al, 2022), Nepal ( Shrestha et al, 2021 ) and in Bangladesh ( Sultana et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, less than half of the participants (47.6%) experienced at least one side effect while remaining study participants (52.38%) experienced more than one side effect. Our study results confirmed that most of the side effects were mild in nature as have been observed in other studies conducted elsewhere ( Shrestha et al, 2021 ; Konu et al, 2021 ; Watcharananan et al, 2022; Sultana et al, 2021 ) including in some African settings ( Konu et al, 2021 ). Our findings of odds of women experiencing more acute and severe AEFI from the Covishield vaccine (ChAdOx1 nCoV-19 vaccine) than males has also been observed in Thailand (Watcharananan et al, 2022), Nepal ( Shrestha et al, 2021 ) and in Bangladesh ( Sultana et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our study results confirmed that most of the side effects were mild in nature as have been observed in other studies conducted elsewhere ( Shrestha et al, 2021 ; Konu et al, 2021 ; Watcharananan et al, 2022; Sultana et al, 2021 ) including in some African settings ( Konu et al, 2021 ). Our findings of odds of women experiencing more acute and severe AEFI from the Covishield vaccine (ChAdOx1 nCoV-19 vaccine) than males has also been observed in Thailand (Watcharananan et al, 2022), Nepal ( Shrestha et al, 2021 ) and in Bangladesh ( Sultana et al, 2021 ). This finding is also consistent with other data published on the COVID-19 vaccine ( Gee et al, 2021 ; Blumenthal et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the overall incidence of adverse events following vaccination was found to be 29.8% which is in contrast to a study conducted in Bangladesh [14]. The incidence of adverse events following vaccination was found to be 2.47% immediately following vaccination, 6.78% experienced adverse reactions in the observation room, and 25.3% experienced reactions after the observation period.…”
Section: Incidence and Side-effects After Vaccinationcontrasting
confidence: 99%
“…Both were within the range of self-report surveys. The former has shown prevalence ranging from 51 to 96% ( 21 , 27 , 35 , 38 , 39 ) and the second one, prevalence ranging from 71 to 82% ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%